SOLVING THE EQUATION OF HEAT DISSIPATION IN A ROD BY THE FINITE ELEMENT METHOD - Mamatov Sh. S; Musurmonov Ahmadjon Latifovich (International Journal on Human-Computing Studies, 2021)
The designer can only achieve the requisite thermal performance of external enclosing structures if they have a thorough understanding of the processes that occur in fences during heat transfer and the ability to employ the right calculations. As you may be aware, a thorough analytical representation of the heat conduction process comprises a differential equation and specified boundary conditions.